Analisis Keterkaitan Rasio Keuangan Daerah Dalam Pengukuran Kinerja Pemerintah Daerah (Studi Kasus Pada Setda Kabupaten Bogor) - Djanegara, Moermahadi Soerja; Wakhyudi, Wakhyudi (STIE Kesatuan, 2007)
The change in the system from a centralized government to a decentralized one, brings about consequences for a change of approach used in local financial management, especially in the areas of fiscal management. Financial balance policy between the central government and local governments, namely, by implementing fiscal decentralization policy. Fiscal decentralization is expected to encourage the participation, initiative, and creativity of local governments and communities to build their own neighborhood. The purpose of this study was to evaluate the performance of local governments within the framework of fiscal decentralization. Several rules have been set by the central government on local government performance evaluation as stipulated in the Regional Government Performance Accountability Report or called LAKIP. However, measuring and evaluating the performance of the government may not merely based on the basis of LAKIP but also on regional financial ratios, as in Bogor district government local revenue and expenditure budget (APBD). Regional financial ratios used are the ratio of independence (fiscal autonomy), the ratio of effectiveness and efficiency ratios, debt service coverage ratio, the ratio of activity, and growth ratios. The results of the calculation of financial ratios of Bogor Regency (Kabupaten Bogor) government budget for the 2003-2006 fiscal year show the local independence and low local growth. However, Bogor Regency government is effective and efficient in using its income. The results of the evaluation in this study indicate that Bogor Regency government is still very dependent to central government to finance them in their activities. This condition shows that the welfare of the people is still low. Even though in the LAKIP, Bogor Regency Government explained that they have been effective and efficient in managing finances, but the number of funds in the budget balance with the central government increases every year. By optimizing the human resources of the local government in accordance to their own skills along with the improvement in evaluating every single working unit, it is expected that each unit may, as the result, improve the government performance in years to come.